Survival Strategies for Culinary MSMEs in the Post-Pandemic Recession: A Case Study on Sellers in Elementary Schools - Irfan Azis; Ani Wahyuni (Al-Makki Publisher, 2025)
The COVID-19 pandemic and subsequent global recession have significantly impacted culinary MSMEs, especially those operating in primary school environments with high dependence on a single market. This study aims to comprehensively identify and analyze the survival strategies developed by culinary MSMEs in the elementary school context in response to the post-pandemic recession. It employs a qualitative approach with an interpretive paradigm to gain an in-depth understanding of the survival strategies of culinary MSMEs within the post-pandemic elementary school environment. Data were collected through in-depth interviews, observations, and focused group discussions over 8 months, then analyzed thematically using the Sustainable Livelihood Approach framework. The findings reveal four key strategies: (1) product and market diversification, (2) extreme operational efficiency, (3) social capital mobilization, and (4) diversification of revenue sources. However, the effectiveness of these strategies is constrained by structural barriers such as limited access to formal financing and digital literacy. The study’s implications emphasize the need for contextual empowerment policies, including unsecured microcredit programs, simple digital training, and the role of school institutions as facilitators to build the resilience of micro MSMEs in limited markets.